Nanometer composite negative electrode material and preparation method thereof

The preparation of MoS2/MWCNTs nanocomposite anode material through electrostatic-assisted self-assembly method has solved the shortcomings of existing materials in terms of energy density and cycle stability, and achieved efficient and environmentally friendly battery material preparation.

CN119673986AActive Publication Date: 2025-03-21胡敏文
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411576093.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-21
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have shortcomings in energy density and cycle stability, especially multi-walled carbon nanotubes (MWCNTs) and molybdenum disulfide (MoS2) materials have large irreversible capacity, smaller specific capacity and poor cycle stability in the first cycle.

Method used

The nanocomposite anode material was prepared by electrostatic-assisted self-assembly method. By self-assembling multi-walled carbon nanotubes and molybdenum disulfide in solution, nanocomposites of MoS2/MWCNTs were formed and heat-treated to remove unnecessary components.

Benefits of technology

The high reversible capacity, good cycle stability and rate performance of nanocomposite anode material are achieved, and the preparation method is efficient, energy-saving and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673986A_ABST
    Figure CN119673986A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium battery negative electrode materials, and discloses a nano composite negative electrode material and a preparation method thereof. The molybdenum disulfide-carbon nanotube composite material comprises the following components in parts by weight: 3-4 parts of carbon nanotubes, 135-150 parts of concentrated nitric acid, 315-330 parts of concentrated sulfuric acid, 600-650 parts of diluted hydrochloric acid, 30-40 parts of absolute ethyl alcohol, 7.5-10 parts of polyethyleneimine, 25-30 parts of molybdenum disulfide, 10-12 parts of a surfactant and 3325-3600 parts of deionized water. A modified MoS2 nanosheet layer and MWCNTs are subjected to self-assembly in a solution by adopting an electrostatic force assisted self-assembly method to obtain a MoS2 / PVP / PEI / MWCNTs quaternary compound, and finally heat treatment is performed to obtain the final MoS2 / MWCNTs nano composite negative electrode material which has relatively high reversible capacity and relatively good cycling stability and rate capability. In addition, the preparation method does not need high-temperature and high-pressure conditions and is efficient, convenient, energy-saving and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery negative electrode materials, and in particular to a nano composite negative electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are considered to be one of the high-energy batteries that can best meet the requirements of sustainable development in the future society. In recent years, lithium-ion batteries have developed rapidly and have been widely used in portable electronic devices such as mobile phones, laptops, and cameras, as well as in the fields of aviation and aerospace, and have received great attention in the field of electric vehicles. However, current lithium-ion batteries cannot meet the growing demand for energy density, such as pure electric vehicles and hybrid electric vehicles. Therefore, the development of battery materials with high energy density and high rate performance has become a research hotspot that has attracted much attention.

[0003] Negative electrode materials are one of the key materials that affect the performance of lithium-ion batteries. At present, the negative electrode materials of lithium-ion batteries mainly include graphite, amorphous carbon, carbon nanotubes, silicon-based materials, tin-based materials, alloy materials, metal oxides and two-dimensional nanomaterials. Among them, multi-walled carbon nanotubes (MWCNTs) are a new type of carbon crystal material discovered in recent years. They are composed of several to thousands of single-walled carbon nanotubes coaxially. The inter-tube force is similar to the van der Waals force of graphite, and the radial spacing between adjacent tubes is about 0.34nm. MWCNTs tubes have excellent physical and chemical properties, such as large specific surface area and molecular-sized cavities, extremely high tensile strength, good thermodynamic properties, high chemical stability and good hydrogen storage performance. Therefore, they have been studied a lot in the fields of catalyst carriers, hydrogen storage materials, lithium-ion batteries, double-layer capacitors and field emission. MWCNTs used as negative electrode materials for lithium-ion batteries have the advantages of many lithium insertion sites, easy lithium removal and good cycle stability, but their irreversible capacity of the first cycle is large and their specific capacity is small.

[0004] Molybdenum disulfide (MoS2) is an important transition metal sulfide with a typical layered structure. It is widely used and can be used as an embedded electrode material for electrochemical lithium storage. It provides a high theoretical specific capacity, but its cycle stability is poor. Therefore, many researchers have hybridized it with carbon materials with excellent cycle stability, such as graphene, carbon nanotubes, amorphous carbon, etc., to obtain composite negative electrode materials with better performance.

[0005] Currently, the hydrothermal synthesis method is usually used to prepare MoS2 / CNTs nanocomposites, but its disadvantages are high temperature and high pressure, which not only places high demands on equipment, but is also extremely energy-consuming and does not meet the requirements of modern green chemistry. Summary of the invention

[0006] In order to overcome the shortcomings and deficiencies of the prior art, the present invention aims to provide a nanocomposite negative electrode material and a preparation method thereof. The prepared nanocomposite negative electrode material has high reversible capacity, good cycle stability and rate performance. The preparation method is an electrostatic force-assisted self-assembly method, which is efficient, convenient, energy-saving and environmentally friendly.

[0007] The technical solution adopted by the present invention to solve its technical problem is: A nano composite negative electrode material comprises, by weight, 3-4 parts of carbon nanotubes, 135-150 parts of concentrated nitric acid, 315-330 parts of concentrated sulfuric acid, 600-650 parts of dilute hydrochloric acid, 30-40 parts of anhydrous ethanol, 7.5-10 parts of polyethyleneimine, 25-30 parts of molybdenum disulfide, 10-12 parts of surfactant, and 3325-3600 parts of deionized water.

[0008] Preferably, the carbon nanotubes are multi-walled carbon nanotubes.

[0009] Preferably, the surfactant is polyvinyl pyrrolidone.

[0010] Preferably, the concentration of the concentrated nitric acid is 65%.

[0011] Preferably, the concentration of the concentrated sulfuric acid is 98%.

[0012] Preferably, the concentration of the dilute hydrochloric acid is 3%.

[0013] The method for preparing a nanocomposite negative electrode material comprises the following steps: (1) Mix concentrated sulfuric acid and concentrated nitric acid and stir them evenly, then add multi-walled carbon nanotubes, ultrasonically disperse them for 10 minutes, and then transfer them to an oil bath for reaction. After the reaction is completed, dilute them with 1000-1200 parts of deionized water, let them stand overnight, filter out the acid solution, and then wash them with 1500 parts of deionized water for 3-4 times, wash them with anhydrous ethanol twice, transfer them to an oven for vacuum drying for 24 hours, then transfer them to a refrigerator for freezing for 5 hours, and then freeze-dry them to obtain pretreated multi-walled carbon nanotubes, add them to 500 parts of deionized water, and ultrasonically disperse them for 15 minutes to obtain a multi-walled carbon nanotube aqueous dispersion; (2) adding polyethyleneimine to 30 times the mass of deionized water and stirring evenly to form a polyethyleneimine aqueous solution, then adding it dropwise to the multi-walled carbon nanotube aqueous dispersion under ultrasonic conditions, continuing ultrasonication for 1.5 hours after the dropwise addition is completed, and removing a small amount of precipitate by centrifugation to obtain a polyethyleneimine-coated multi-walled carbon nanotube aqueous dispersion; (3) Adding molybdenum disulfide and polyvinyl pyrrolidone to 100 parts of deionized water and stirring evenly, then ultrasonically dispersing until the dispersion turns dark green, standing for 72 hours, removing the upper clear liquid and transferring it to a centrifuge tube, centrifuging at 1500 rpm for 45 minutes, and then removing the upper clear liquid to obtain a polyvinyl pyrrolidone-stabilized molybdenum disulfide nanosheet dispersion; (4) Under ultrasonic conditions, the dispersion of molybdenum disulfide nanosheets was dropwise added to the aqueous dispersion of polyethyleneimine-coated multi-walled carbon nanotubes. After the addition was completed, the dispersion was ultrasonically treated for 1.5 h, and then allowed to stand for 24 h. The mixture was filtered and dried in a vacuum oven for 24 h to obtain a quaternary complex of molybdenum disulfide / polyvinyl pyrrolidone / polyethyleneimine / multi-walled carbon nanotubes. The mixture was then heat treated at 800 °C for 1.5 h in an inert gas atmosphere to remove polyvinyl pyrrolidone and polyethyleneimine to obtain a nanocomposite negative electrode material of molybdenum disulfide / multi-walled carbon nanotubes.

[0014] Preferably, the reaction in step (1) is carried out at 70° C. with stirring for 6 hours.

[0015] Preferably, the centrifugal operation in step (2) is a centrifugal operation with a rotation speed of 8000 r / min and a time of 5 min.

[0016] Preferably, the oven in step (1) is an oven at 60°C, and the oven in step (4) is an oven at 80°C.

[0017] Beneficial effects of the present invention: The present invention uses polyvinyl pyrrolidone (PVP) as a surfactant, and assists in liquid-phase ultrasonic exfoliation to prepare a PVP-stabilized MoS2 nanosheet dispersion, and the nanosheet is negatively charged, and then the acidified multi-walled carbon nanotubes (MWCNTs) are coated with polyethyleneimine (PEI) to make their surfaces positively charged, and then the two components are self-assembled in the solution to obtain a MoS2 / PVP / PEI / MWCNTs quaternary complex, and finally heat-treated to obtain the final MoS2 / MWCNTs nanocomposite negative electrode material, which has a high reversible capacity, good cycle stability and rate performance. In addition, the preparation method is a self-assembly method assisted by electrostatic interaction, which is efficient, convenient, energy-saving and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is the cycle performance diagram of each material electrode at the same current density; Figure 2 This is the rate performance diagram of MoS2 / MWCNTs nanocomposite negative electrode material at different current densities; DETAILED DESCRIPTION

[0019] The concept and technical effects of the present invention will be clearly and completely described below in conjunction with embodiments to fully understand the purpose, features and effects of the present invention. Embodiment 1:

[0020] A nano composite negative electrode material, whose raw materials, measured by weight, include: 3 parts of multi-walled carbon nanotubes, 135 parts of concentrated nitric acid, 315 parts of concentrated sulfuric acid, 600 parts of dilute hydrochloric acid, 30 parts of anhydrous ethanol, 7.5 parts of polyethyleneimine, 25 parts of molybdenum disulfide, 10 parts of polyvinyl pyrrolidone, and 3325 parts of deionized water.

[0021] The method for preparing the nanocomposite negative electrode material described in this embodiment comprises the following steps, in parts by weight: (1) Mix concentrated sulfuric acid and concentrated nitric acid and stir them evenly, then add multi-walled carbon nanotubes, ultrasonically disperse them for 10 minutes, then transfer them to an oil bath and stir them at 70°C for 6 hours. After the reaction is completed, dilute them with 1000 parts of deionized water, let them stand overnight, filter out the acid solution, then wash them with 1500 parts of deionized water for 3-4 times, wash them with anhydrous ethanol twice, transfer them to a 60°C oven and vacuum dry them for 24 hours, then transfer them to a refrigerator and freeze them for 5 hours, and then freeze-dry them to obtain pretreated multi-walled carbon nanotubes, add them to 500 parts of deionized water, ultrasonically disperse them for 15 minutes, and obtain a multi-walled carbon nanotube aqueous dispersion; (2) adding polyethyleneimine to 30 times the mass of deionized water and stirring evenly to form a polyethyleneimine aqueous solution, then adding it dropwise to the multi-walled carbon nanotube aqueous dispersion under ultrasonic conditions, continuing ultrasonication for 1.5 hours after the dropwise addition is completed, and removing a small amount of precipitate by centrifugation at a speed of 8000 r / min for 5 minutes to obtain a polyethyleneimine-coated multi-walled carbon nanotube aqueous dispersion; (3) Adding molybdenum disulfide and polyvinyl pyrrolidone to 100 parts of deionized water and stirring evenly, then ultrasonically dispersing until the dispersion turns dark green, standing for 72 hours, removing the upper clear liquid and transferring it to a centrifuge tube, centrifuging at 1500 rpm for 45 minutes, and then removing the upper clear liquid to obtain a polyvinyl pyrrolidone-stabilized molybdenum disulfide nanosheet dispersion; (4) Under ultrasonic conditions, the dispersion of molybdenum disulfide nanosheets was added drop by drop into the aqueous dispersion of polyethyleneimine-coated multi-walled carbon nanotubes. After the addition was completed, the dispersion was ultrasonicated for 1.5 h, and then allowed to stand for 24 h. The dispersion was filtered and dried in a vacuum oven at 80 °C for 24 h to obtain a quaternary complex of molybdenum disulfide / polyvinyl pyrrolidone / polyethyleneimine / multi-walled carbon nanotubes. The mixture was then heat treated at 800 °C for 1.5 h in an inert gas atmosphere to remove polyvinyl pyrrolidone and polyethyleneimine to obtain a nanocomposite negative electrode material of molybdenum disulfide / multi-walled carbon nanotubes. Embodiment 2:

[0022] A nano composite negative electrode material, whose raw materials, measured by weight, include: 3 parts of multi-walled carbon nanotubes, 140 parts of concentrated nitric acid, 325 parts of concentrated sulfuric acid, 625 parts of dilute hydrochloric acid, 35 parts of anhydrous ethanol, 9 parts of polyethyleneimine, 27 parts of molybdenum disulfide, 11 parts of polyvinyl pyrrolidone, and 3470 parts of deionized water.

[0023] The method for preparing the nanocomposite negative electrode material described in this embodiment comprises the following steps, in parts by weight: (1) Mix concentrated sulfuric acid and concentrated nitric acid and stir them evenly, then add multi-walled carbon nanotubes, ultrasonically disperse them for 10 minutes, then transfer them to an oil bath and stir them at 70°C for 6 hours. After the reaction is completed, dilute them with 1100 parts of deionized water, let them stand overnight, filter out the acid solution, then wash them with 1500 parts of deionized water for 3-4 times, wash them with anhydrous ethanol twice, transfer them to a 60°C oven and vacuum dry them for 24 hours, then transfer them to a refrigerator and freeze them for 5 hours, and then freeze-dry them to obtain pretreated multi-walled carbon nanotubes, add them to 500 parts of deionized water, ultrasonically disperse them for 15 minutes, and obtain a multi-walled carbon nanotube aqueous dispersion; (2) adding polyethyleneimine to 30 times the mass of deionized water and stirring evenly to form a polyethyleneimine aqueous solution, then adding it dropwise to the multi-walled carbon nanotube aqueous dispersion under ultrasonic conditions, continuing ultrasonication for 1.5 hours after the dropwise addition is completed, and removing a small amount of precipitate by centrifugation at a speed of 8000 r / min for 5 minutes to obtain a polyethyleneimine-coated multi-walled carbon nanotube aqueous dispersion; (3) Adding molybdenum disulfide and polyvinyl pyrrolidone to 100 parts of deionized water and stirring evenly, then ultrasonically dispersing until the dispersion turns dark green, standing for 72 hours, removing the upper clear liquid and transferring it to a centrifuge tube, centrifuging at 1500 rpm for 45 minutes, and then removing the upper clear liquid to obtain a polyvinyl pyrrolidone-stabilized molybdenum disulfide nanosheet dispersion; (4) Under ultrasonic conditions, the dispersion of molybdenum disulfide nanosheets was added drop by drop into the aqueous dispersion of polyethyleneimine-coated multi-walled carbon nanotubes. After the addition was completed, the dispersion was ultrasonicated for 1.5 h, and then allowed to stand for 24 h. The dispersion was filtered and dried in a vacuum oven at 80 °C for 24 h to obtain a quaternary complex of molybdenum disulfide / polyvinyl pyrrolidone / polyethyleneimine / multi-walled carbon nanotubes. The mixture was then heat treated at 800 °C for 1.5 h in an inert gas atmosphere to remove polyvinyl pyrrolidone and polyethyleneimine to obtain a nanocomposite negative electrode material of molybdenum disulfide / multi-walled carbon nanotubes. Embodiment 3:

[0024] A nano composite negative electrode material, whose raw materials, measured by weight, include: 4 parts of multi-walled carbon nanotubes, 150 parts of concentrated nitric acid, 330 parts of concentrated sulfuric acid, 650 parts of dilute hydrochloric acid, 40 parts of anhydrous ethanol, 10 parts of polyethyleneimine, 30 parts of molybdenum disulfide, 10-12 parts of polyvinyl pyrrolidone, and 3600 parts of deionized water.

[0025] The method for preparing the nanocomposite negative electrode material described in this embodiment comprises the following steps, in parts by weight: (1) Mix concentrated sulfuric acid and concentrated nitric acid and stir them evenly, then add multi-walled carbon nanotubes, ultrasonically disperse them for 10 minutes, then transfer them to an oil bath and stir them at 70°C for 6 hours. After the reaction is completed, dilute them with 1200 parts of deionized water, let them stand overnight, filter out the acid solution, then wash them with 1500 parts of deionized water for 3-4 times, wash them twice with anhydrous ethanol, transfer them to a 60°C oven and vacuum dry them for 24 hours, then transfer them to a refrigerator and freeze them for 5 hours, and then freeze-dry them to obtain pretreated multi-walled carbon nanotubes, add them to 500 parts of deionized water, ultrasonically disperse them for 15 minutes, and obtain a multi-walled carbon nanotube aqueous dispersion; (2) adding polyethyleneimine to 30 times the mass of deionized water and stirring evenly to form a polyethyleneimine aqueous solution, then adding it dropwise to the multi-walled carbon nanotube aqueous dispersion under ultrasonic conditions, continuing ultrasonication for 1.5 hours after the dropwise addition is completed, and removing a small amount of precipitate by centrifugation at a speed of 8000 r / min for 5 minutes to obtain a polyethyleneimine-coated multi-walled carbon nanotube aqueous dispersion; (3) Adding molybdenum disulfide and polyvinyl pyrrolidone to 100 parts of deionized water and stirring evenly, then ultrasonically dispersing until the dispersion turns dark green, standing for 72 hours, removing the upper clear liquid and transferring it to a centrifuge tube, centrifuging at 1500 rpm for 45 minutes, and then removing the upper clear liquid to obtain a polyvinyl pyrrolidone-stabilized molybdenum disulfide nanosheet dispersion; (4) Under ultrasonic conditions, the dispersion of molybdenum disulfide nanosheets was added drop by drop into the aqueous dispersion of polyethyleneimine-coated multi-walled carbon nanotubes. After the addition was completed, the dispersion was ultrasonicated for 1.5 h, and then allowed to stand for 24 h. The dispersion was filtered and dried in a vacuum oven at 80 °C for 24 h to obtain a quaternary complex of molybdenum disulfide / polyvinyl pyrrolidone / polyethyleneimine / multi-walled carbon nanotubes. The mixture was then heat treated at 800 °C for 1.5 h in an inert gas atmosphere to remove polyvinyl pyrrolidone and polyethyleneimine to obtain a nanocomposite negative electrode material of molybdenum disulfide / multi-walled carbon nanotubes.

[0026] Comparative Example 1: The difference between this comparative example and Example 1 is that MWCNTs are not added during the preparation process, and the remaining raw materials and steps are the same as those in Example 1, and a MoS2 single-component negative electrode material is prepared.

[0027] Comparative Example 2: The difference between this comparative example and Example 1 is that MoS2 is not added during the preparation process, and the remaining raw materials and steps are the same as those in Example 1, and a MWCNTs single-component negative electrode material is prepared.

[0028] Negative electrode material performance test: The negative electrode materials prepared in Example 1 and Comparative Examples 1-2, the conductive agent carbon black and the adhesive PVDF were used to prepare the electrode paste in a mass ratio of 85:10:5: PVDF was first dissolved in NMP solvent, then carbon black and each negative electrode material were added, fully mixed and diluted with NMP solvent to a suitable viscosity. Then the electrode paste was evenly coated on a copper foil current collector with a thickness of 0.1nm, dried in an oven at 110°C for 4h, taken out and pressed firmly on a double-roll press, and then cut into a circular copper foil with a diameter of 1.2cm, which was the electrode sheet used for the test. With metal lithium foil as the counter electrode, Celgard-2300 lithium-ion battery separator as the separator, 1.0M LiPF6 EC / EMC / DMC solution (volume ratio 1:1:1) as the electrolyte system, a homemade battery was assembled under an inert gas environment. Then the performance test was carried out on a Landian charge and discharge tester (LAND CT2001A). The current density of the charge and discharge test was 100 mA / g, and the voltage range was 3.0-0.0 V. The scan rate of the cyclic voltammetry test was 0.2 mV / s, and the voltage range was 3.0-0.0 V.

[0029] Figure 1 This is the cycle performance diagram of three negative electrode materials at 100mA / g. As can be seen from the figure, MoS2 material shows low specific capacity and poor cycle stability, and MWCNTs material shows low specific capacity and excellent cycle stability. This is because MoS2 has a typical layered structure and can be used as an embedded electrode material for electrochemical lithium storage, providing a high theoretical specific capacity, but its cycle stability is poor; MWCNTs used as negative electrode materials for lithium-ion batteries have the advantages of many lithium insertion sites, easy lithium removal, and good cycle stability, but its irreversible capacity of the first cycle is large and its specific capacity is small. The MoS2 / MWCNTs nanocomposite negative electrode material organically combines the two components and interacts with each other, showing a high specific capacity and good cycle stability.

[0030] Figure 2The figure shows the rate performance of three negative electrode materials at different current densities. The current densities for 1-5, 6-10, 11-15, 16-20 and 21-30 cycles are 100mA / g, 200mA / g, 400mA / g, 800mA / g and 200mA / g respectively. It can be seen from the figure that when the current density changes from 800mA / g to 200mA / g, the MoS2 / MWCNTs nanocomposite negative electrode material can recover to more than 90% of the initial specific capacity value, showing a good performance rate, good reversible capacity, and basically no capacity decay in subsequent cycle tests, showing good cycle stability.

[0031] The above embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work shall all fall within the scope of protection of the present invention.

Claims

1. A nanocomposite negative electrode material, characterized in that: The raw materials include, by weight, 3-4 parts of carbon nanotubes, 135-150 parts of concentrated nitric acid, 315-330 parts of concentrated sulfuric acid, 600-650 parts of dilute hydrochloric acid, 30-40 parts of anhydrous ethanol, 7.5-10 parts of polyethyleneimine, 25-30 parts of molybdenum disulfide, 10-12 parts of surfactant, and 3325-3600 parts of deionized water.

2. A nanocomposite negative electrode material according to claim 1, characterized in that: The carbon nanotubes are multi-walled carbon nanotubes.

3. The nanocomposite negative electrode material according to claim 1, characterized in that: The surfactant is polyvinyl pyrrolidone.

4. The nanocomposite negative electrode material according to claim 1, characterized in that: The concentration of the concentrated nitric acid is 65%.

5. The nanocomposite negative electrode material according to claim 1, characterized in that: The concentration of the concentrated sulfuric acid is 98%.

6. The nanocomposite negative electrode material according to claim 1, characterized in that: The concentration of the dilute hydrochloric acid is 3%.

7. The method for preparing a nanocomposite negative electrode material according to claim 6, characterized in that: The preparation method comprises the following steps: (1) Mix concentrated sulfuric acid and concentrated nitric acid and stir them evenly, then add multi-walled carbon nanotubes, ultrasonically disperse them for 10 minutes, and then transfer them to an oil bath for reaction. After the reaction is completed, dilute them with 1000-1200 parts of deionized water, let them stand overnight, filter out the acid solution, and then wash them with 1500 parts of deionized water for 3-4 times, wash them with anhydrous ethanol twice, transfer them to an oven for vacuum drying for 24 hours, then transfer them to a refrigerator for freezing for 5 hours, and then freeze-dry them to obtain pretreated multi-walled carbon nanotubes, add them to 500 parts of deionized water, and ultrasonically disperse them for 15 minutes to obtain a multi-walled carbon nanotube aqueous dispersion; (2) adding polyethyleneimine to 30 times the mass of deionized water and stirring evenly to form a polyethyleneimine aqueous solution, then adding it dropwise to the multi-walled carbon nanotube aqueous dispersion under ultrasonic conditions, continuing ultrasonication for 1.5 hours after the dropwise addition is completed, and removing a small amount of precipitate by centrifugation to obtain a polyethyleneimine-coated multi-walled carbon nanotube aqueous dispersion; (3) Adding molybdenum disulfide and polyvinyl pyrrolidone to 100 parts of deionized water and stirring evenly, then ultrasonically dispersing until the dispersion turns dark green, standing for 72 hours, removing the upper clear liquid and transferring it to a centrifuge tube, centrifuging at 1500 rpm for 45 minutes, and then removing the upper clear liquid to obtain a polyvinyl pyrrolidone-stabilized molybdenum disulfide nanosheet dispersion; (4) Under ultrasonic conditions, the dispersion of molybdenum disulfide nanosheets was dropwise added to the aqueous dispersion of polyethyleneimine-coated multi-walled carbon nanotubes. After the addition was completed, the dispersion was ultrasonically treated for 1.5 h, and then allowed to stand for 24 h. The mixture was filtered and dried in a vacuum oven for 24 h to obtain a quaternary complex of molybdenum disulfide / polyvinyl pyrrolidone / polyethyleneimine / multi-walled carbon nanotubes. The mixture was then heat treated at 800 °C for 1.5 h in an inert gas atmosphere to remove polyvinyl pyrrolidone and polyethyleneimine to obtain a nanocomposite negative electrode material of molybdenum disulfide / multi-walled carbon nanotubes.

8. The method for preparing a nanocomposite negative electrode material according to claim 7, characterized in that: The reaction in step (1) is carried out by stirring at 70° C. for 6 hours.

9. The method for preparing a nanocomposite negative electrode material according to claim 7, characterized in that: The centrifugal operation in step (2) is a centrifugal operation with a rotation speed of 8000 r / min and a time of 5 min.

10. The method for preparing a nanocomposite negative electrode material according to claim 7, characterized in that: The oven in step (1) is a 60°C oven, and the oven in step (4) is a 80°C oven.

Citation Information

Patent Citations

  • Lithium-ion-battery multiwalled carbon nanotube / molybdenum disulfide combination electrode and preparation method

    CN106711413A

  • Application of high-molecular coating in aluminium negative electrode, aluminium negative electrode, preparation method thereof and secondary battery

    CN108155363A

  • Preparation methods and detection methods of nanocomposite and ZEN electrochemical aptamer sensor

    CN109470761A

  • Preparation method and application of functionalized high-specific-capacity silicon-carbon negative electrode material based on polyethyleneimine and polydopamine copolymer

    CN114824238A

  • Nanocomposite for secondary battery and method of producing the same

    KR1020160097026A